Answer:
5 (1+1)=5 (2)=10
Step-by-step explanation:
you just substitute both X and Y with 1 and calculate it
Answer:
9a+18=9
9a=-9
a=-1
Step-by-step explanation:
Answer:
1st and 3rd and 5th
Step-by-step explanation:
Answer:
a=-5
Step-by-step explanation:
divide both sides by -2: -5=a
a=-5
<span>Question 3
Solve for d.
13d + 4 = 43
13d = 39
d = 3
answer
A. 3
</span><span>Question 4
Solve for r.
4r - 6 = 30
4r = 36
r = 9
answer
D. 9
</span>
<span>Question 5
Solve for u.
126 = 6u
u = 126/6
u = 21
answer
B. 21
</span>